Reasons for Using Electronic Nicotine Delivery Systems by Young People - I. V. Ostrovskaya; N. G. Kostsova; A. K. Khozhatova (Здоровье мегаполиса)
Research shows that there is an increase in the number of young people who have never smoked before, but now use electronic nicotine delivery systems (ENDS). Therefore, it seems relevant to study the reasons for using electronic cigarettes.A theoretical analysis of the problem allowed us to describe the main reasons for using electronic systems. An empirical study involving students of the Medical Institute of the Patrice Lumumba Peoples' Friendship University revealed the reasons among future health workers. The main reason for starting to use ENDS among the respondents was stress. 58.3% of participants noted that it was the reason to start smoking e-cigarettes. Other reasons included smokers in the social circle; attempts to quit smoking regular cigarettes; a desire to copy adults and attempts to protect others from secondhand smoke exposure.